Studi Kasus Pembentukan Karakter Akhlakul Karimah Siswa Melalui Pembiasaan Sikap di PPTQ Muhammadiyah Ibnu Juraimi - Ardelia Khoirunnisa Ardiningrum; Hikmatul Maula; Veri Jamilatun Hasanah; Muhammad Fahim Ridho; Wahyu Kholis Prihantoro (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
Islamic boarding schools (pesantren) play a strategic role in shaping the character and noble character of the younger generation amidst the increasingly sophisticated currents of modernization and digital challenges. This study aims to examine the process of character formation of students' noble character through habituation of attitudes at the Muhammadiyah Ibnu Juraimi PPTQ, as well as to understand the strategies, challenges, and roles of various parties in supporting this character development. The research method used is a qualitative approach with a case study type, through participatory observation, in-depth interviews, and documentation. The results of the study indicate that habituation of attitudes is the main strategy, which is realized through teacher role models, enforcement of discipline, routine worship such as qiyamullail, sunnah fasting, recitation of the Qur'an, and social habits such as respect and the use of Islamic greetings. The main challenges in implementing guidance are differences in student backgrounds, the motivation of administrators who still lack awareness in guiding children, and the negative influence of gadgets. Efforts to resolve this are carried out by limiting gadget access, strengthening role models, and involving students' guardians in supporting children's development. The conclusion of this study confirms that the formation of noble character is a long process that requires consistent habituation, contributions between teachers, students, administrators, and guardians of students, as well as overcoming external challenges wisely.